ASHABIYAH IBNU KHALDUN DAN RELEVANSINYA DENGAN NASIONALISME DI INDONESIA - Hanna Widayani (Manthiq : Jurnal Filsafat Agama dan Pemikiran Islam, 2017)
The problem in this research is how ‘Ashabiyah Ibn Khaldun and how’ ashabiyah Ibn Khaldun and its relevance to nationalism in Indonesia.The purpose of this research is to describe the concept of ‘Ashabiyah Ibn Khaldun  and  describes how  its relevance to Indonesian nationalism. The type of this research is library research and  the  method used  in this research is descriptive qualitative.  The  results  of this research are, first; ‘Ashabiyah is defined  by Ibn Khaldun  as social  solidarity. According to Ibn Khaldun  social  solidarity or a sense of class connected by blood  relation  or other  linkage  that has the same meaning and  purpose. This is because blood  ties have  a binding  force  in most  humans, which  makes them  feel the  pain  that  affects them.  Ashabiyya is a feeling of one  group  or social  solidarity, which  arises  naturally  in human life due  to a blood  relation  or revelation affinity. Such  feelings  of love give rise to a sense of destiny,  mutuality,  mutual loyalty, mutual  need, especially  when faced  with calamities or threats  of the  enemy, or to achieve certain goals. Then Ibn Khaldun argues  that it is impossible to create a state  without  the support  of a strong sense of unity and  solidarity. The process of its founding  requires a real struggle, a battle  of life and  death. Solidarity (‘asabiya)  is principally  co-operation and  please help  the  group  closely in such  a way that the  members  of each  group are not only assisting but willing to sacrifice  life for the common good. And this according to him is a natural  phenomenon for humans in the process of the establishment of the state. Second; The relevance or relationship between ‘Ashabiyah Ibn Khaldun/  social  solidarity  with  Indonesian nationalism in modern times  is, lies in its components. Which  in the ‘Ashabiyah, Ibn Khaldun  positioned the society  or nation  as a starting point to build a state, which  then in truth the community both have a high spirit to fight for the ideals of the nation and state. Because the goal of Indonesian nationalism itself is nothing but to arouse the sense of brotherhood / kinship in the Indonesian nation,  and always keep  the national  identity as a form of the love of the nation and the country.